Exterior product and method of manufacturing the same
By forming a specific fine concave and convex structure on the surface of the titanium or titanium alloy metal substrate and landing the anodized film, the problem of difficult to form a dark appearance without metallic luster in the prior art is solved, and the effects of high uniformity and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202380064483.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-05
- Filing Date
- 2023-09-01
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to form a dark appearance such as black without metallic luster with high uniformity, especially in the manufacturing process of watch parts, and it is difficult to achieve a dark appearance without metallic luster.
A fine concave and convex film is formed on the surface of the metal base material of titanium or titanium alloy, the average height of the convex portion is 5 nm to 50 μm, and the ratio of the average height to the average width of the convex portion is 0.25 or more, and an anodized film is formed by landfilling the fine concave and convex.
It achieves a dark appearance such as black without metallic luster with high uniformity, and improves corrosion resistance of the exterior products.
Smart Images

Figure CN119768566A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an exterior product having an anodic oxide film formed on the surface of a metal substrate and a method for producing the same. Background Art
[0002] Conventionally, as a component having an anodic oxide film formed on the surface of a metal substrate, there is a watch component disclosed in Patent Document 1. In this watch component, the particle size of the crystals contained in titanium or a titanium alloy is 7 μm or more and 3 mm or less, the surface of each crystal is formed as a mirror surface, the normal direction of each crystal surface is formed to be different from each other, and an anodic oxide film is formed on the surface.
[0003] Moreover, when manufacturing the watch parts of Patent Document 1, after heat treating titanium or a titanium alloy to coarsen the grain size of multiple crystals to be greater than 7 μm and less than 3 mm, etching is performed to mirror the surface of each crystal and make the normal directions of the surface of each crystal different from each other, and after the etching process, the surface is anodized to form an anodized film.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 5971890 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In addition, in the manufacturing method of the watch component of patent document 1, by forming an anodic oxide film after implementing etching to make the surface mirror-finished and make the normal direction of each crystal surface different, it is possible to give the surface of the watch component a metallic luster of a specific color. However, on the contrary, it is difficult to form a dark appearance such as black without metallic luster. Depending on the product, a dark appearance without metallic luster is also desired in most cases, and an exterior product with a dark appearance such as black without metallic luster is required to be formed with high uniformity.
[0009] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide an exterior product capable of forming an appearance of a dark color such as black without metallic luster with high uniformity, and a method for manufacturing the same.
[0010] Means for solving problems
[0011] The exterior product of the present invention is characterized in that the average height of the convex portion is set to 5nm to 50μm on the surface of the metal substrate of titanium or titanium alloy to form fine concavo-convex, the convex portion is formed in a manner such that the ratio of the average height of the convex portion to the average width of the convex portion is 0.25 or more, and the anodic oxide film is formed in a manner such that the fine concavo-convex is buried. The average height of the convex portion of the fine concavo-convex formed on the surface of the metal substrate is more preferably 50nm to 2000nm, and further preferably 50nm to 1000nm.
[0012] Thus, when the surface of titanium or titanium alloy is mirror-finished, a metallic luster can be obtained. In contrast, by forming fine concavoconvex on the surface of the metal substrate, light can be scattered on the surface of the metal substrate to reduce the luster, and a dark appearance with a matte texture can be obtained. Furthermore, by setting the average height of the convex portion to 5nm to 50μm and the ratio of the average height of the convex portion to the average width of the convex portion to 0.25 or more to form fine concavoconvex, a dark appearance such as black without metallic luster can be reliably formed with high uniformity. In addition, by forming an anodic oxide film in a manner that fills the fine concavoconvex, a dark appearance of desired coloring and corrosion resistance of the exterior product can be obtained.
[0013] The exterior product of the present invention is characterized in that the average width of the convex portions is 1500 nm or less, more preferably 1200 nm or less.
[0014] This makes it possible to more reliably form a dark color appearance such as black without metallic luster with high uniformity.
[0015] The exterior product of the present invention is characterized in that the film thickness of the anodic oxide film from the top of the protrusion is 500 nm or less, more preferably 10 nm to 500 nm.
[0016] Thus, by setting the film thickness of the anodic oxide film from the top of the protrusion to 500 nm or less, the dark color visibility of the metal substrate can be ensured, the desired dark color appearance can be more reliably obtained, and the corrosion resistance of the exterior product can be more reliably obtained.
[0017] The manufacturing method of the exterior product of the present invention is characterized by comprising: a first step of removing a natural oxide film from the surface of a metal substrate of titanium or a titanium alloy; a second step of etching the surface of the metal substrate to form fine concavo-convex portions on the surface of the metal substrate in a manner such that the average height of the convex portions is 5nm to 50μm and the ratio of the average height of the convex portions to the average width of the convex portions is 0.25 or more; and a third step of forming an anodic oxide film in a manner of filling the fine concavo-convex portions. The average height of the convex portions of the fine concavo-convex portions formed on the surface of the metal substrate is more preferably 50nm to 1000nm.
[0018] Thus, when the surface of titanium or titanium alloy is mirror-finished, a metallic luster can be obtained. In contrast, by forming fine concavoconvex on the surface of the metal substrate, light can be scattered on the surface of the metal substrate and the gloss can be reduced, and a dark appearance with a matte texture can be obtained. Furthermore, by setting the average height of the convex portion to 5nm to 50μm and the ratio of the average height of the convex portion to the average width of the convex portion to be 0.25 or more to form fine concavoconvex, a dark appearance such as black without metallic luster can be reliably formed with high uniformity. In addition, by forming an anodic oxide film in a manner of filling the fine concavoconvex, a dark appearance of the desired coloring and corrosion resistance of the exterior product can be obtained. In addition, by removing the natural oxide film from the surface of the metal substrate in advance, a uniform dark appearance can be obtained more reliably.
[0019] Effects of the Invention
[0020] According to the present invention, a dark color appearance such as black without metallic luster can be formed on the surface of an exterior product with high uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 (a) is a schematic cross-sectional view of an exterior product according to an embodiment of the present invention, and (b) is a partial enlarged view of (a).
[0022] Figure 2 (a) to (e) are schematic process drawings showing the manufacturing process of the exterior product according to the embodiment.
[0023] Figure 3 This is a graph showing the relationship between the ratio of the average height H of the convex portions to the average width W of the convex portions and the reflectivity in Examples and Comparative Examples.
[0024] Figure 4 This is a graph showing the relationship between the average width W of the convex portions and the reflectivity in Examples and Comparative Examples. DETAILED DESCRIPTION
[0025] [Exterior product and manufacturing method thereof according to the embodiment]
[0026] like Figure 1 As shown, the exterior product 1 according to the embodiment of the present invention has a metal substrate 2 formed of titanium or a titanium alloy, fine concavo-convex 21 is formed on the surface of the metal substrate 2, and an anodic oxide film 3 is formed on the surface side of the metal substrate 2 in a manner that fills the fine concavo-convex 21.
[0027] The average height H of the convex portion 22 of the fine asperities 21 formed on the surface of the metal substrate 2 is, for example, 5 nm to 50 μm, more preferably 50 nm to 2000 nm, and further preferably 50 nm to 1000 nm. In addition, the average width W of the convex portion 22 of the fine asperities 21 is, for example, 100 nm to 2000 nm, preferably the average width W of the convex portion 22 is 1500 nm or less, more preferably 1200 nm or less, for example, the average width W of the convex portion 22 is preferably 200 nm to 1200 nm. And, the convex portion 22 in the formation area of the fine asperities 21 is formed in such a manner that the ratio of the average height H of the convex portion 22 to the average width W of the convex portion 22, that is, (average height H of the convex portion 22 / average width W of the convex portion 22) is 0.25 or more.
[0028] In addition, the average spacing P between adjacent convex portions 22, 22 of the fine concavo-convex 21 formed on the surface of the metal substrate 2 is, for example, 1500 nm or less, preferably 0 nm to 1200 nm. It should be noted that the average height H of the convex portion 22, the average width W of the convex portion 22, and the average spacing P between the convex portions 22, 22 are values calculated from the average values obtained by measuring the fine concavo-convex shapes of multiple locations on the surface of the titanium material using an atomic force microscope (AFM).
[0029] The film thickness T of the anodized film 3 from the protrusion 22 is about tens to hundreds of nm, and the film thickness T of the anodized film 3 from the top of the protrusion 22 in the present embodiment is 10 nm to 500 nm. In addition, the film thickness T of the anodized film 3 from the protrusion 22 refers to the film thickness from the top of the protrusion 22 to the outer surface of the anodized film 3, and the film thickness is measured by cross-sectional observation using a transmission electron microscope (TEM).
[0030] When manufacturing the exterior product 1 of this embodiment, Figure 2 As shown in (a) and (b), the metal substrate 2m of titanium or titanium alloy as the base material is degreased to remove the oil stain 4. Figure 2 As shown in (b) and (c), the natural oxide film 5 is removed from the surface of the metal substrate 2m of titanium or titanium alloy. The removal treatment of the natural oxide film 5 uses, for example, DAIN TIA (manufactured by Yamato Chemical Industry, containing 10 wt% or less nitric acid and 2.8 wt% hydrofluoric acid) as an oxide film remover, and the metal substrate 2m of titanium or titanium alloy is immersed in the original solution of DAIN TIA for about 1 minute at room temperature to remove the natural oxide film 5.
[0031] Then, if Figure 2As shown in (c) and (d) of FIG. 5 , the surface of the metal substrate 2m from which the natural oxide film 5 has been removed is etched, for example, so that the average height H of the protrusions 22 is 5 nm to 50 μm, and the ratio of the average height of the protrusions 22 to the average width of the protrusions 22 is 0.25 or more, so that fine concavo-convex 21 is formed, and the metal substrate 2 is obtained. In the process of etching the surface of the metal substrate 2m to form the fine concavo-convex 21, for example, DAIN TIB-SL (manufactured by Yamato Chemical Industry, containing less than 1 wt% of hydrofluoric acid) is used as an etchant, and the metal substrate 2m of titanium or titanium alloy is immersed in the stock solution of DAIN TIB-SL for about 3 to 10 minutes at room temperature to form the fine concavo-convex 21.
[0032] In addition, it is also preferred to immerse the metal substrate 2m in sulfuric acid to perform both the removal treatment of the natural oxide film 5 from the surface of the metal substrate 2m and the treatment of etching the surface of the metal substrate 2m to form the fine concavo-convex 21 at one time. In this case, for example, 98% concentrated sulfuric acid is diluted to 500mL / L of sulfuric acid at 50°C±2°C, and the metal substrate 2m is immersed in the sulfuric acid for about 10 minutes to 30 minutes to remove the natural oxide film 5 and form the fine concavo-convex 21.
[0033] Then, if Figure 2 As shown in (e), an anodic oxide film 3 is formed on the surface side of the metal substrate 2 in a manner that fills the fine concavo-convex 21, thereby obtaining an exterior product 1. In the formation process of the anodic oxide film 3, for example, CPE (chlorinated polyethylene)-3000A (Liocle-N, manufactured by Mitsubishi Gas Chemical Trading Co., Ltd.) is diluted to a concentration of 500 mL / L to prepare an electrolyte, and the metal substrate 2 is immersed in the electrolyte at room temperature and connected to the anode, and the voltage is 20 V and the current is 5 A / dm 2 A current is passed through the anode for about 1 minute to form an anodic oxide film 3 on the metal substrate 2 .
[0034] According to the exterior product 1 of the present embodiment, when the surface of titanium or titanium alloy is mirror-finished, metallic luster can be obtained. In contrast, by forming the fine concavo-convex 21 on the surface of the metal substrate 2, light can be scattered on the surface of the metal substrate 2 to reduce the luster, and a dark appearance with a matte texture can be obtained. Furthermore, the average height of the convex portion 22 is formed to 5nm to 50μm, more preferably 50nm to 2000nm, and further preferably 50nm to 1000nm, and the ratio of the average height H of the convex portion 22 to the average width W of the convex portion 22 is set to 0.25 or more to form the fine concavo-convex 21, thereby reliably forming a dark appearance such as black without metallic luster with high uniformity. In addition, by forming the anodic oxide film 3 in a manner that fills the fine concavo-convex 21, a dark appearance of desired coloring and corrosion resistance of the exterior product 1 can be obtained.
[0035] In addition, by setting the film thickness T of the anodized film 3 from the top of the protrusion 22 to less than 500 nm, preferably to 10 nm to 500 nm, the visual recognizability of the dark color of the metal substrate 2 can be ensured, the dark color appearance of the desired color can be obtained more reliably, and the corrosion resistance of the exterior product 1 can be obtained more reliably.
[0036] Furthermore, in the method for manufacturing the exterior product 1 , by removing the oil stains 4 and the natural oxide film 5 from the surface of the metal substrate 2 m in advance, it is possible to more reliably obtain a uniform dark appearance of the exterior product 1 .
[0037] [Examples and Comparative Examples]
[0038] The embodiments and comparative examples of the exterior product 1 of the present invention are described. The embodiments and comparative examples are shown in Table 1. The metal substrates of each of Examples 1 to 4 and Comparative Example 1 use plate-shaped pure titanium (JIS 1 type), and the average height H and average width W of the convex portions of the fine concave-convex portions formed on the surface of each metal substrate are measured by observation using an atomic force microscope (AFM). In addition, the film thickness T of the colorless and transparent anodized film formed in a manner to fill the fine concave-convex is measured by observing the cross section using a transmission electron microscope (TEM). The spectral reflectance at the peak wavelength is the spectral reflectance (SCI) between 360nm and 740nm measured for each sample of the exterior product 1 of Examples 1 to 4 and Comparative Example 1 using a spectrophotometer, and the reflectance at the wavelength (peak wavelength) with the maximum spectral reflectance is extracted.
[0039]
[0040] Example 1
[0041] The sample of Example 1 was prepared as follows: DAIN TIA (manufactured by Yamato Chemical Industry, containing less than 10wt% nitric acid and 2.8wt% hydrofluoric acid) was used as an oxide film remover, and a metal substrate of pure titanium (JIS 1 type) was immersed in a stock solution of DAIN TIA for 1 minute at room temperature, and the natural oxide film was removed from the metal substrate and the surface of the substrate was etched before the fine concave-convex formation stage. The metal substrate from which the natural oxide film was removed was immersed in a stock solution of DAIN TIB-SL (manufactured by Yamato Chemical Industry, containing less than 1wt% hydrofluoric acid) for 3 minutes at room temperature, and an etching treatment was performed to form fine concave-convex. Furthermore, CPE-3000A (RIOCRY-N, manufactured by Mitsubishi Gas Chemical Trading Co., Ltd.) was diluted to a concentration of 500mL / L to prepare an electrolyte, and the metal substrate was immersed in the electrolyte at room temperature and connected to the anode, and the voltage was 20V and the current was 5A / dm 2 Electric current was passed through the anode for 1 minute to form an anodic oxide film.
[0042] Example 2
[0043] The sample of Example 2 was prepared as follows: DAIN TIA (manufactured by Yamato Chemical Industry, containing less than 10wt% nitric acid and 2.8wt% hydrofluoric acid) was used as an oxide film remover, and a metal substrate of pure titanium (JIS type 1) was immersed in a stock solution of DAIN TIA for 1 minute at room temperature, and the natural oxide film was removed from the metal substrate and the surface of the substrate was etched before the fine concave-convex formation stage. The metal substrate from which the natural oxide film was removed was immersed in a stock solution of DAIN TIB-SL (manufactured by Yamato Chemical Industry, containing less than 1wt% hydrofluoric acid) for 10 minutes at room temperature, and an etching treatment was performed to form fine concave-convex. Furthermore, CPE-3000A (RIOCRY-N, manufactured by Mitsubishi Gas Chemical Trading Co., Ltd.) was diluted to a concentration of 500mL / L to prepare an electrolyte, and the metal substrate was immersed in the electrolyte at room temperature and connected to the anode, and the voltage was 20V and the current was 5A / dm 2 Electric current was passed through the anode for 1 minute to form an anodic oxide film.
[0044] Example 3
[0045] The sample of Example 3 was prepared as follows: 98% concentrated sulfuric acid was diluted to a concentration of 500 mL / L, the diluted sulfuric acid was heated to 50°C ± 2°C, the pure titanium material was immersed for 10 minutes to remove the natural oxide film and form fine concave-convex, and then CPE-3000A (RIOCRY-N, manufactured by Mitsubishi Gas Chemical Trading Co., Ltd.) was diluted to a concentration of 500 mL / L to prepare an electrolyte, the metal substrate was immersed in the electrolyte at room temperature and connected to the anode, and the voltage was 20 V and the current was 5 A / dm 2 An electric current was passed through the anode for 1 minute to form an anodic oxide film.
[0046] Example 4
[0047] The sample of Example 4 was prepared as follows: 98% concentrated sulfuric acid was diluted to a concentration of 500 mL / L, and after heating to 50°C ± 2°C, the pure titanium material was immersed for 30 minutes to remove the natural oxide film and form fine concave-convex. Then, CPE-3000A (RIOCRY-N, manufactured by Mitsubishi Gas Chemical Trading Co., Ltd.) was diluted to a concentration of 500 mL / L to prepare an electrolyte, and the metal substrate was immersed in the electrolyte at room temperature and connected to the anode, with a voltage of 20 V and a current of 5 A / dm 2 Electric current was passed through the anode for 1 minute to form an anodic oxide film.
[0048] Comparative Example 1
[0049] The sample of Comparative Example 1 was prepared as follows: the pure titanium material was immersed in an aqueous solution containing 3% hydrogen peroxide, 10% ammonium monohydrogen fluoride, and 5% sulfuric acid for 1 minute, and the surface roughness was adjusted by removing the natural oxide film and etching. Then, the pure titanium material was immersed in an aqueous solution containing 10% hydrogen peroxide, 5% ammonium monohydrogen fluoride, and 5% sulfuric acid for 1 minute, and acid cleaning was performed. Furthermore, CPE-3000A (RIOCRY-N, manufactured by Mitsubishi Gas Chemical Trading Co., Ltd.) was diluted to a concentration of 500mL / L to prepare an electrolyte, and the metal substrate was immersed in the electrolyte at room temperature and connected to the anode, and the voltage was 20V and the current was 5A / dm 2 Electric current was passed through the anode for 1 minute to form an anodic oxide film.
[0050] Figure 3 : is a graph showing the relationship between the ratio of the average height H of the convex portion to the average width W of the convex portion and the reflectivity of Examples 1 to 4 and Comparative Example 1, Figure 4 This is a graph showing the relationship between the average width W of the convex portions and the reflectivity in Examples 1 to 4 and Comparative Example 1.
[0051] like Figure 3 As shown, it can be seen that when the ratio of the average height H of the fine concave-convex portions to the average width W of the convex portions, that is, (average height H of the convex portions / average width W of the convex portions) is greater than 0.25, the spectral reflectivity of the peak wavelength is less than 20%, and a high level of dark appearance can be obtained.
[0052] In addition, if Figure 4 As shown, it can be seen that when the average width W of the convex parts of the fine concavoconvex is 1200 nm or less, the spectral reflectance of the peak wavelength is 20% or less, and a dark appearance of a higher level can be obtained.
[0053] [Scope of the invention disclosed in this specification]
[0054] In addition to the various inventions and embodiments listed as inventions, the invention disclosed in this specification also includes inventions determined by changing the contents of these parts to other contents disclosed in this specification within the scope of application, or inventions determined by adding other contents disclosed in this specification to these contents, or inventions determined by deleting the contents of these parts to the extent that some effects can be obtained and then forming a higher level concept. In addition, the invention disclosed in this specification also includes the following modified examples and additional contents.
[0055] For example, the surface shape of the metal substrate of the exterior product to which the present invention is applied is suitably flat, curved, or multi-faceted.
[0056] Industrial Applicability
[0057] The present invention can be used for various exterior products that are visually recognized from the outside, such as tableware such as bottles, cups, straws, and spoons, building components, and vehicle components.
[0058] Description of Reference Numerals
[0059] 1…Exterior product 2, 2m…Metal substrate 21…Fine irregularities 22…Protrusions 3…Anodic oxide film 4…Oil stains 5…Natural oxide film H…Average height of the protrusions of the fine irregularities W…Average width of the protrusions of the fine irregularities P…Average distance between adjacent protrusions of the fine irregularities T…Thickness of the anodized film from the top of the protrusions
Claims
1. An exterior product, characterized in that: Fine concavities and convexities are formed on the surface of a metal substrate of titanium or titanium alloy so that the average height of the convexities is 5 nm to 50 μm. The convex portions are formed so that the ratio of the average height of the convex portions to the average width of the convex portions is 0.25 or more, The anodic oxide film is formed so as to fill the fine irregularities.
2. The exterior product according to claim 1, characterized in that: The average width of the convex portions is 1500 nm or less.
3. The exterior product according to claim 1 or 2, characterized in that: The film thickness of the anodic oxide film from the top of the protrusion is 500 nm or less.
4. A method for manufacturing an exterior product, characterized in that: have: The first step is to remove the natural oxide film from the surface of the metal substrate of titanium or titanium alloy; A second step of etching the surface of the metal substrate to form fine concavo-convex portions on the surface of the metal substrate in such a manner that the average height of the convex portions is 5 nm to 50 μm and the ratio of the average height of the convex portions to the average width of the convex portions is 0.25 or more; and In the third step, an anodic oxide film is formed so as to fill the fine irregularities.
Citation Information
Patent Citations
Thermosensitive recording material
JP1984071890A